Poliquetos de fondos duros (Polychaeta) de bahías de Huatulco y Puerto Angel, Oaxaca, México - Gómez, Patricia (Universidad de Costa Rica, 1997)
Distribution, abundance and diversity of polychaetes were studied at the tourism centers of Huatulco and Puerto Angel Bays, East Tropical Pacific of Mexico. All specimens were hand-collected by SCUBA divers, along transects perpendicular to tbe coast. The areas sampled were characterized by a rocky bottom and corals o f tbe genera Pocillopora. An inventory of 7 1 polychaetes species i s presented, based o n 884 specimens, tbat belong to nine orders and 19 families. The dominant species were: Pseudovermilia occidentalis, Hydroides brachyacantha, Ceratonereis singularis, Trypanosyllis taeniaformis and Phyllodoce lamellifera, which was present at all transects sampled. Over 24 species had a frequency greater tban 60%. Diversity was higher in Puerto Angel (H'=3.05, 1=0.89), and abundance was higher in Cacaluta (292 organisms), followed by La Entrega (265 organisms). Species richness was similar for all localities except for El Maguey. The soutbem distribution range o f Polycirrus mexicanus and Pseudopotamilla debilis, previously set a t tbe Sea o f Cortez, is here extended t o tb e Gulf of Tehuantepec. A cluster analysis showed tbat Puerto Angel and Tangolunda had tbe highest similarity (0.42). Botb places share rock-coral facies, 16 species, and human environmental impacts. Caculata and El Maguey had the lowest similarity (0.04) and the highest evenness, sharing only one species. When compared to tbe mollusk communities at tbe same sites, tbe polychaetes studied were less diverse but presented a higher evenness. Compared to Cabo Pulmo, Sea of Cortez, a similar environment dominated by Pocillopora, tbe present polychaete community has a more diverse but less abundant. However, two shared species, T. taeniaformis and Eunice lucei. had a similar abundance in tbese two areas.